The Relationship of Parental Knowledge to Booster Immunization in Infants Aged 2 Years - Lisnawati, Lilis; Sutarno, Maryati (Indonesian Journal of Global Health Research, 2024)
Follow-up immunization in infants under two years old (Baduta) aged 18 months given immunization (DPT-HB-Hib and Measles / MR), Immunization is currently estimated to prevent 2 to 3 million deaths each year. The main obstacle to the success of the immunization program in infants is the low awareness of mothers who have babies to bring their children to be immunized. The purpose of this study was to determine the relationship between parents' knowledge of booster immunization in baduta at UPTD Puskesmas (community health center) Banjar Agung Serang City, Banten for the October-December 2023 period. This study used correlation analytical method with cross sectional approach. The population used in this study was mothers who had toddlers as many as 224 people. The samples used amounted to 114 mothers using accidental sampling techniques that meet the criteria of inclusion and exclusion. Parental knowledge independent variable, booster immunization dependent variable, the data were collected using questionnaires, data processing with chi square. The results showed that there is a significant relationship between parents' knowledge of participation in Booster immunization at Baduta at the Banjar Agung Health Center, Serang City, Banten Province in 2023 with a P-value of 0.000 and an OR value of 10.082, which means that BADUTA mothers who have poor knowledge have a 10 times greater risk of not giving Booster immunization in cubs compared with mothers who have good knowledge.